2021
DOI: 10.3390/cryst12010056
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments on Relaxor-PbTiO3 Ferroelectric Crystals

Abstract: Numerous investigations on the development of the relaxor-PbTiO3 ferroelectric crystals have been carried out since their extraordinary properties were revealed. Recent developments on these crystals have offered further advances in electromechanical applications. In this review, recent developments on relaxor-PbTiO3 crystals and their practical applications are reviewed. The single crystal growth methods are first discussed. Two different strategies, poling and doping, for piezoelectric improvement are survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 218 publications
(420 reference statements)
0
5
0
Order By: Relevance
“…On the otherhand, the continuousfeeding Bridgman growth method which is able to better control the composition has been developed to reduce compositional segregation. [23][24][25][26][27] However, the continuousfeeding Bridgman method has only been applied to improving compositional uniformity so far.…”
Section: Introductionmentioning
confidence: 99%
“…On the otherhand, the continuousfeeding Bridgman growth method which is able to better control the composition has been developed to reduce compositional segregation. [23][24][25][26][27] However, the continuousfeeding Bridgman method has only been applied to improving compositional uniformity so far.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite-type ABO 3 (A = Ba, Sr, Pb) oxides’ crystal structure as well as their physical and optical characteristics have been thoroughly explored recently, owing to their widespread development and their functional properties suitable for many technological applications [ 1 , 2 , 3 ]. In particular, PbTiO 3 itself has been frequently and intensively studied due to its excellent physical properties, which makes it a promising material for a variety of applications, including ferroelectric memory cells [ 4 , 5 ], optoelectronic devices [ 6 , 7 ], dielectric capacitors [ 8 ], electromechanical devices [ 9 , 10 ] and pyroelectric applications [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1960s, relaxor ferroelectrics have remained in the scientific focus because of their exceptional physical properties [1], such as high dielectric permittivity, large polarization and pyroelectricity, and significant electromechanical response [2][3][4][5][6][7]. Recently, it was shown that they also possess large caloric properties [8][9][10].…”
Section: Introductionmentioning
confidence: 99%